Aghradu al-Saja’ fi al-Qur’an al-Karim (Dirasah Tahliliyah Badi’iyyah fi Surati al-Muzzammil) - Maula, Inayatul; Nurawaliyah, Pina (AlFaqrah: Journal of Arabic Studies, 2025)
This research includes a study of Badi’iyyah studies which is one of the types of studies in the ilm al-Balaghah. Ilm al-Badi’ is concerned with improving speech in terms of expression and meaning. One of the elements within the field of "Badi’iyah" is "Saja’," which involves concluding every two or more sentences with a single letter. Many rhetoricians have differed in their views on "Saja’" Some have called for avoiding it due to its complexity and resemblance to the poetry of the pre-Islamic era (Jahiliyya), while others have seen a rhetorical aspect in it after it was mentioned in the Quran. The objectives of this research are to identify the verses that contain "Saja’" and their rhetorical purposes. It becomes evident that this research is a qualitative study using the documentary method. The methodology used in this research is descriptive and rhetorical analysis, especially in the field of "Badiyah," to analyze the data. As a result of this research, the forms of verses containing "Saja’" have been identified, including the interrupted and parallel forms, along with their rhetorical purposes in Surah Al-Muzzammil, which involve improving their expressions, emphasizing certain aspects, and describing things through the mentioned "Saja’."